Nonaqueous electrolyte solution, electrochemical device, and electronic device
By using a specific proportion of chain and cyclic carbonate in the non-aqueous electrolyte of lithium-ion batteries, combining electrolytes and specific compounds, the transmission capacity of lithium ions is optimized, the problem of large lithium ion transmission resistance in the prior art is solved, and efficient discharge and high-temperature storage performance is achieved.
Patent Information
- Application Number
- CN202510005605.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
When existing lithium-ion batteries use chain ester compounds to improve the dissociation capacity of lithium salts, they lead to an increase in the viscosity of the nonaqueous electrolyte, thereby increasing the transmission resistance of lithium ions, affecting the high efficiency and high-temperature storage performance of the battery.
By using a specific proportion of chain carbonate and cyclic carbonate in the nonaqueous electrolyte, combining lithium hexafluorophosphate and lithium difluorosulfonimide, the transmission capacity of lithium ions is optimized, and the stability and protection properties of the electrolyte are improved through vinylene carbonate and specific compounds of formula I and formula II.
It realizes efficient transmission of lithium ions in non-aqueous electrolyte, improves the large-rate discharge performance and high-temperature storage performance of the electrochemical device, and reduces the volume expansion caused by side reactions and over-discharge storage gas production.
Smart Images

Figure BDA0005227067770000032 
Figure BDA0005227067770000041 
Figure BDA0005227067770000042
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a non-aqueous electrolyte, an electrochemical device and an electronic device. Background Art
[0002] As people's demand for electronic products increases year by year, lithium-ion batteries, as the power source of electronic products, are playing an increasingly important role in our daily lives. The high power performance of lithium-ion batteries depends on the transmission ability of lithium ions in non-aqueous electrolytes. The existing technology, while using chain ester compounds to improve the dissociation ability of lithium salts in non-aqueous electrolytes, often leads to an increase in the viscosity of non-aqueous electrolytes, which in turn increases the transmission resistance of lithium ions. Therefore, it is imperative to provide lithium-ion batteries with high-efficiency battery transmission capabilities. Summary of the invention
[0003] The embodiments of the present application provide a non-aqueous electrolyte, an electrochemical device, and an electronic device, which achieve excellent high-rate discharge performance while improving high-temperature storage performance.
[0004] In a first aspect, an embodiment of the present application provides a non-aqueous electrolyte, the non-aqueous electrolyte comprising a linear carbonate and a cyclic carbonate, the linear carbonate comprising dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, the cyclic carbonate comprising at least one of ethylene carbonate and propylene carbonate; based on the total mass of the non-aqueous electrolyte, the mass percentage of dimethyl carbonate is M1%, 0.001≤M1≤0.1; the mass percentage of ethyl methyl carbonate is M2%, 15≤M2≤60; the mass percentage of diethyl carbonate is M3%, 5≤M3≤35; the mass percentage of ethylene carbonate is M4%, and the mass percentage of propylene carbonate is M5%, 20≤M4+M5≤40.
[0005] Based on the non-aqueous electrolyte of the embodiment of the present application, the inventors found that when the non-aqueous electrolyte includes the above-mentioned chain carbonate and cyclic carbonate, and the mass percentage of each chain carbonate and cyclic carbonate in the non-aqueous electrolyte is controlled to meet the above-mentioned range, the cyclic carbonate can undergo solvation with lithium ions to improve the dissociation ability of lithium salts; the chain ester solvent has low viscosity, and a high content of chain carbonate can weaken the migration resistance of solvated lithium ions, thereby improving the transmission capacity of lithium ions in the non-aqueous electrolyte; at the same time, the specific ratio of the chain carbonate can inhibit the continuous occurrence of the ester exchange reaction of ethyl methyl carbonate → dimethyl carbonate + diethyl carbonate, reduce the oxidative decomposition of the chain carbonate, improve its stability, and promote the efficient transmission of lithium ions in the non-aqueous electrolyte, thereby improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0006] In some embodiments, the non-aqueous electrolyte satisfies at least one of the following conditions: (1) 20≤M2≤50; (2) 40≤M2+M3≤66; (3) Based on the above embodiments, the present application adjusts the mass percentage content M2% of ethyl methyl carbonate and its mass percentage content M3% of diethyl carbonate and the mass percentage content M1% of dimethyl carbonate to meet any of the above conditions, thereby further improving the stability of the chain carbonate while improving the dissociation ability of the lithium salt, thereby further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0007] In some embodiments, the non-aqueous electrolyte includes at least one of lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI). Based on the total mass of the non-aqueous electrolyte, the mass percentage of lithium hexafluorophosphate is M6%, the mass percentage of lithium bis(fluorosulfonyl)imide is M7%, 2.5≤M6≤25, 15≤M6+M7≤25. Based on the above embodiments, a specific amount of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide is further added to the non-aqueous electrolyte of the present application. Due to the large anion volume of LiFSI and the non-concentrated charge density distribution, it is similar to Li + The binding between them is weak, which is more conducive to dissociation and provides higher conductivity. At the same time, LiFSI can form an interfacial protection film containing low-impedance components such as Li3N or Li2S on the electrode surface. The two work together with the above-mentioned electrolyte system to further improve the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0008] In some embodiments, the non-aqueous electrolyte satisfies:
[0009] Based on the above embodiments, the present application adjusts the relationship between the mass percentage of ethylene carbonate M4%, the mass percentage of propylene carbonate M5%, the mass percentage of lithium hexafluorophosphate M6% and the mass percentage of lithium bis(fluorosulfonyl)imide M7% in the non-aqueous electrolyte to meet the above range, thereby further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0010] In some embodiments, the non-aqueous electrolyte includes vinylene carbonate; based on the total mass of the non-aqueous electrolyte, the mass percentage of vinylene carbonate is E%, and 0.001≤E≤0.05. Based on the above embodiments, when the non-aqueous electrolyte of the present application further includes vinylene carbonate and its mass content is within the above range, the organic SEI film formed by reduction polymerization during the negative electrode film formation process has good stability, which can improve the protection of the negative electrode and reduce the side reactions on the positive electrode, thereby improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device, and inhibiting the volume expansion caused by over-discharge storage gas production.
[0011] In some embodiments, the non-aqueous electrolyte comprises a compound of formula I:
[0012]
[0013] Among them, R 11 , R 12 , R 13 and R 14 are independently selected from H, F, C1 to C3 alkyl or fluorine-substituted C1 to C3 alkyl, and R 11 , R 12 , R 13 or R 14 At least one of them is a fluorine atom; based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of formula I is a%, 0.01≤a≤1. In some embodiments, the compound of formula I is selected from at least one of the following compounds:
[0014]
[0015] Based on the above embodiments, the non-aqueous electrolyte of the present application further includes the above-mentioned compound of formula I, and when its mass content is within the above-mentioned range, the compound of formula I can participate in reduction film formation at the negative electrode. During the film formation process, the F-containing group in the structure of the compound of formula I can form LiF, thereby reducing the impedance of the negative electrode SEI film formation and having a good negative electrode film formation effect, thereby further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device, and inhibiting the volume expansion caused by over-discharge storage gas production.
[0016] In some embodiments, the non-aqueous electrolyte comprises a compound of formula II:
[0017]
[0018] Among them, R 21 , R 22 , R 23 , R 24 , R 25 and R 26 Independently selected from H, F, C1 to C3 alkyl or fluorine-substituted C1 to C3 alkyl; based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of formula II is b%, 2≤b≤4. In some embodiments, the compound of formula II includes at least one of the following compounds:
[0019]
[0020] Based on the above embodiments, the non-aqueous electrolyte of the present application further includes the compound of Formula II and the mass content is within the above range. The compound of Formula II can enter the lithium ion solvation layer, preferentially form a film on the positive electrode, inhibit the oxidative decomposition of the solvent in the non-aqueous electrolyte on the positive electrode, reduce the increase in impedance caused by the by-products after solvent oxidation, relieve the gas generation in the fully charged state of the battery cell, thereby further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device, and inhibiting the volume expansion caused by over-discharge storage gas generation.
[0021] In a second aspect, an embodiment of the present application provides an electrochemical device, including a positive electrode sheet, a negative electrode sheet, and the above non-aqueous electrolyte; the positive electrode sheet includes a positive electrode current collector and a positive electrode mixture layer provided on at least one surface of the positive electrode current collector, and the negative electrode includes a negative electrode current collector and a negative electrode mixture layer provided on at least one surface of the negative electrode current collector; the positive electrode active material in the positive electrode mixture layer includes Li x Ni y M 1-y O 2-z A z , 0.98 ≤ x ≤ 1.1, 0.53 ≤ y ≤ 0.95, 0 < z ≤ 0.05. Based on the total mass of the positive electrode mixture layer, the mass percentage content of nickel element is n%, 33 ≤ n ≤ 56. Wherein, M is selected from at least one of aluminum element, magnesium element, manganese element, cobalt element, iron element, chromium element, vanadium element, titanium element, copper element, calcium element, zinc element, zirconium element, niobium element, molybdenum element, strontium element, antimony element, tungsten element or bismuth element; A is selected from at least one of fluorine element, phosphorus element, sulfur element, boron element, silicon element or chlorine element. Based on the above embodiments, the electrochemical device of the present application uses a positive electrode active material, which can cooperate with the electrolyte to make the lithium ion insertion and extraction speeds of the positive and negative electrodes match, realize better charge and discharge performance, thereby further improving the high-rate discharge performance of the electrochemical device and taking into account the improvement of high-temperature storage performance.
[0022] In a third aspect, an embodiment of the present application provides an electronic device, which includes the above electrochemical device Detailed Embodiments
[0023] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0024] An embodiment of the present application provides an electrochemical device, including a non-aqueous electrolyte, a positive electrode, a negative electrode, and a separator.
[0025] Non-aqueous electrolyte
[0026] The non-aqueous electrolyte used in the electrochemical device of the embodiment of the present application includes an electrolyte and a solvent for dissolving the electrolyte. In some embodiments, the non-aqueous electrolyte includes a linear carbonate and a cyclic carbonate, the linear carbonate includes dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate. In some embodiments, based on the total mass of the non-aqueous electrolyte, the mass percentage of dimethyl carbonate is M1%, 0.001≤M1≤0.1. For example, M1 is 0.001, 0.004, 0.01, 0.03, 0.07, 0.1 or a value within the range of any two of these values. The mass percentage of ethyl methyl carbonate is M2%, 15≤M2≤60. Preferably, 20≤M2≤50. For example, M2 is 15, 20, 21, 32, 38, 45, 50, 58, 60 or a value within the range of any two of these values. The mass percentage of diethyl carbonate is M3%, 5≤M3≤35. For example, M3 is 5, 6, 16, 27, 30, 35 or a value within the range of any two of these values. 40≤M2+M3≤66, for example, the sum of the mass percentage of ethyl methyl carbonate M2% and the mass percentage of diethyl carbonate M3% can be 40, 46, 52, 59, 60, 63, 66 or a value within the range of any two of these values. In some embodiments, In some of these embodiments, In some of these embodiments, In some of these embodiments, The mass percentage of ethylene carbonate is M4%, the mass percentage of propylene carbonate is M5%, and 20≤M4+M5≤40. For example, M4+M5 is 20, 25, 28, 32, 36, 40 or a value in the range formed by any two of these values. When the non-aqueous electrolyte includes the above-mentioned linear carbonate and cyclic carbonate, and the mass percentage of each linear carbonate and cyclic carbonate in the non-aqueous electrolyte is controlled to meet the above-mentioned range, the efficient transmission of lithium ions in the non-aqueous electrolyte can be promoted, and the high-rate discharge performance and high-temperature storage performance of the electrochemical device can be improved.
[0027] In some of the embodiments, the non-aqueous electrolyte includes at least one of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide; based on the total mass of the non-aqueous electrolyte, the mass percentage of lithium hexafluorophosphate is M6%, the mass percentage of lithium bisfluorosulfonyl imide is M7%, 2.5≤M6≤25, 15≤M6+M7≤25. For example, M6 can be a value within the range of 2.5, 6.8, 10, 14, 23, 25 or any two of these values. M6+M7 can be a value within the range of 15, 16, 18, 22, 24, 25 or any two of these values. The non-aqueous electrolyte further includes a specific content of lithium hexafluorophosphate and lithium bisfluorosulfonyl imide, which can further improve the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0028] In some embodiments, the non-aqueous electrolyte satisfies In some of these embodiments, In some of these embodiments, In some of these embodiments, The relationship between the mass percentage of ethylene carbonate, the mass percentage of propylene carbonate, the mass percentage of lithium hexafluorophosphate and the mass percentage of lithium bis(fluorosulfonyl)imide in the non-aqueous electrolyte satisfies the above range, which can further improve the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0029] In some of the embodiments, the non-aqueous electrolyte includes vinylene carbonate. Based on the total mass of the non-aqueous electrolyte, the mass percentage of vinylene carbonate is E%, and 0.001≤E≤0.05. For example, the value of E can be 0.001, 0.008, 0.015, 0.029, 0.041, 0.05, or a value within the range composed of any two of these values. When the non-aqueous electrolyte further includes vinylene carbonate, and its mass content is within the above range, it can enhance the protective effect on the negative electrode, while reducing the side reactions on the positive electrode, thereby improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device, while taking into account the suppression of volume expansion caused by over-discharge storage and gas production.
[0030] In some embodiments, the non-aqueous electrolyte comprises a compound of formula I:
[0031]
[0032] Among them, R 11 , R 12 , R 13 and R 14 are independently selected from H, F, C1 to C3 alkyl or fluorine-substituted C1 to C3 alkyl, and R 11 , R 12 , R 13 or R14 At least one of them is a fluorine atom; based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of formula I is a%, 0.01≤a≤1. For example, the value of a can be 0.01, 0.19, 0.34, 0.46, 0.82, 1, or a value in the range of any two of these values. In some embodiments, the compound of formula I is selected from at least one of the following compounds:
[0033]
[0034] The non-aqueous electrolyte further includes a compound of formula I, and when its mass content is within the above range, it has a good negative electrode film-forming effect, thereby further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device, while taking into account the suppression of volume expansion caused by over-discharge storage gas production.
[0035] In some embodiments, the non-aqueous electrolyte comprises a compound of formula II:
[0036]
[0037] Among them, R 21 , R 22 , R 23 , R 24 , R 25 and R 26 Independently selected from H, F, C1 to C3 alkyl or fluorine-substituted C1 to C3 alkyl; based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of formula II is b%, 2≤b≤4. For example, the value of b can be 2, 2.3, 2.6, 3.3, 3.8, 4 or a value within the range of any two of these values. In some embodiments, the compound of formula II includes at least one of the following compounds:
[0038]
[0039]
[0040] The non-aqueous electrolyte further includes the above-mentioned compound of formula II, which can further inhibit the oxidative decomposition of the solvent in the non-aqueous electrolyte at the positive electrode, reduce the oxidative decomposition of vinylene carbonate at the positive electrode and the influence of HF generated by the decomposition of the compound of formula I itself on the positive electrode, thereby further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device, while taking into account the inhibition of volume expansion caused by over-discharge storage gas production.
[0041] The non-aqueous electrolyte may also include other non-aqueous solvents. The present application has no particular restrictions on the type of the non-aqueous solvent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of other carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The carbonate compound may include but is not limited to at least one of other chain carbonate compounds or other cyclic carbonate compounds.
[0042] The above-mentioned other linear carbonate compounds may include but are not limited to at least one of dipropyl carbonate, methylpropyl carbonate or ethylpropyl carbonate. The above-mentioned other cyclic carbonate compounds may include but are not limited to at least one of butylene carbonate or vinylethylene carbonate.
[0043] The above-mentioned carboxylic acid ester compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone.
[0044] The above-mentioned ether compound may include, but is not limited to, at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran.
[0045] The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0046] positive electrode
[0047] The positive electrode includes a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material in the positive electrode mixture layer includes Li x Ni y M 1-y O 2-z A z, where 0.98 ≤ x ≤ 1.1, 0.53 ≤ y ≤ 0.95, and 0 < z ≤ 0.05. Based on the total mass of the positive electrode mixture layer, the mass percentage of nickel element is n%, satisfying 33 ≤ n ≤ 56. For example, the value of n can be 33, 34, 38, 40, 46, 48, 52, 56, or a value within the range formed by any two of these values. Among them, M is selected from at least one of aluminum element, magnesium element, manganese element, cobalt element, iron element, chromium element, vanadium element, titanium element, copper element, calcium element, zinc element, zirconium element, niobium element, molybdenum element, strontium element, antimony element, tungsten element, or bismuth element; A is selected from at least one of fluorine element, phosphorus element, sulfur element, boron element, silicon element, or chlorine element. The electrochemical device using the above positive electrode active material can cooperate with the non-aqueous electrolyte to match the lithium ion insertion and extraction rates of the positive and negative electrodes, achieving better charge and discharge performance, and further improving the high-rate discharge performance and high-temperature storage performance of the electrochemical device.
[0048] In some embodiments, the positive electrode material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of the positive electrode conductive material may include, but are not limited to, carbon blacks such as acetylene black and Super-P; amorphous carbons such as needle coke; materials such as carbon nanotubes; graphene, etc. The above positive electrode conductive materials can be used alone or in any combination.
[0049] In some embodiments, the positive electrode material layer includes a positive electrode binder; the type of the positive electrode binder is not particularly limited. In the case of the coating method, any material that can be dissolved or dispersed in the liquid medium used during electrode manufacturing is acceptable. Examples of the positive electrode binder may include, but are not limited to, one or more of the following: resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutene rubber, and ethylene-propylene rubber; thermoplastic elastomer-like polymers such as styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer or its hydride; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, and propylene-α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer; polymer compositions having ionic conductivity of alkali metal ions, etc. The above positive electrode binders can be used alone or in any combination.
[0050] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0051] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0052] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0053] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0054] negative electrode
[0055] The negative electrode comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.
[0056] The negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO w(0.5<w<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.
[0057] The negative electrode material layer of the present application also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0058] The negative electrode material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0059] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0060] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0061] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.
[0062] Diaphragm
[0063] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode, and the diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.
[0064] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.
[0065] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0066] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0067] The present application also provides an electronic device, which includes the secondary battery of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0068] Example
[0069] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the electrochemical device of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0070] Example 1-1
[0071] (1) Preparation of positive electrode
[0072] The positive electrode active material Li 1.08 Ni 0.57 Co 0.16 Mn 0.31 Al 0.0004 O 1.998 S 0.002 , conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) was added. The mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet with a single-sided coating of a positive electrode mixture layer, and the single-sided coating weight was 12.5mg / cm 2 Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode mixture layer on both sides. Then, cold pressing, striping, cutting, and welding the pole ears are used to obtain the desired positive electrode sheet.
[0073] (2) Preparation of non-aqueous electrolyte
[0074] In a dry argon atmosphere glove box, LiPF6 was dissolved in a mixed solution of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate and propylene carbonate to obtain a non-aqueous electrolyte. The mass percentages of LiPF6 and each compound based on the total mass of the non-aqueous electrolyte are shown in Table 1.
[0075] (3) Preparation of negative electrode
[0076] Artificial graphite was used as the negative electrode active material. The negative electrode active material, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), carbon nanotubes (CNT), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95.8:2.4:0.5:0.5:0.8, and then deionized water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 45wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried to obtain a negative electrode sheet with a single-sided coating of a negative electrode mixture layer, and the single-sided coating weight was 7.5mg / cm 2Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode mixture layer on both sides. Then, cold pressing, striping, cutting, and welding the tabs are performed to obtain the desired negative electrode sheet.
[0077] (4) Preparation of diaphragm: A porous polyethylene film with a thickness of 15 μm was used as the diaphragm.
[0078] (5) Preparation of lithium-ion batteries: stack the positive electrode sheet, negative electrode sheet and separator in order, place the separator between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and wind them to obtain an electrode assembly. Place the electrode assembly in a packaging bag, inject electrolyte, and package. After a process of storage, formation, degassing, trimming, and capacity testing, a lithium-ion battery is obtained.
[0079] <Test Method>
[0080] (1) 4C rate discharge test
[0081] At 25°C, the formed lithium-ion battery was charged to 4.35V at a constant current rate of 0.2C, then charged at a constant voltage until the current was less than or equal to 0.05C, then left to stand for 30 minutes, and then discharged to 3.0V at a constant current rate of 0.2C, and the 25°C 0.2C rate discharge capacity of the lithium-ion battery was obtained by testing; at 25°C, the lithium-ion battery was charged to 4.35V at a constant current rate of 0.2C, then charged at a constant voltage until the current was less than or equal to 0.05C, and left to stand for 60 minutes; discharged to 3.0V at a constant current rate of 4C, and the 25°C 4C rate discharge capacity of the lithium-ion battery was obtained by testing.
[0082] 25°C 4C rate discharge capacity retention rate of lithium ion secondary battery %=25°C 4C rate discharge capacity / 25°C 0.2C rate discharge capacity×100%.
[0083] (2) High temperature storage performance test
[0084] At 25°C, the formed lithium-ion battery is charged at a constant current of 0.5C to a voltage of 4.35V, then at a constant current of 1C to 4.35V, and then at a constant voltage to a current of 0.05C, and the battery thickness d1 is recorded at this time; then the lithium-ion battery is placed in a high-temperature furnace at a temperature of 80°C. After 48 hours, the battery cell is taken out and the battery thickness d2 is immediately tested at this time.
[0085] High temperature storage thickness expansion rate % = (d2-d1) / d1×100%.
[0086] (3) Changes in gas thickness during over-discharge storage
[0087] At 25°C, the formed lithium-ion battery was charged at a constant current of 0.5C to a voltage of 4.35V, then charged at a constant current of 1C to 4.35V, then charged at a constant voltage to a current of 0.05C, then discharged at 0.2C to 3.0V, left to stand for 15 minutes, and then discharged at 0.02C to 3.0V, and the battery thickness D1 was recorded at this time; then the lithium-ion battery was placed in a high-temperature furnace at a temperature of 60°C. After being placed for 30 days, the battery cell was taken out and the battery thickness D2 was immediately tested at this time.
[0088] High temperature storage thickness expansion rate % = (D2-D1) / D1 x 100%.
[0089] The lithium ion batteries of the following embodiments or comparative examples differ from those of embodiment 1-1 only in that the mass percentage of each substance in the electrolyte is adjusted according to Table 1, and if there is a surplus, the surplus is propyl acetate. The performance test results of the lithium ion batteries of the embodiments and comparative examples are shown in Table 1 below.
[0090] Table 1
[0091]
[0092]
[0093] *In the table above:
[0094] Relational formula 1 = (100M1 + M3) / M2, the calculation result is rounded to 2 decimal places;
[0095] Relational formula 2 = (M4 / 86.06+M5 / 102.09) / (M6 / 151.91+M7 / 187.07), the calculation result is rounded to 2 decimal places;
[0096] As can be seen from Table 1, the lithium ion battery prepared in the embodiment of the present application has an excellent rate discharge capacity retention rate and a lower high-temperature storage gas production thickness change rate when the mass percentage M1% of dimethyl carbonate in the electrolyte satisfies 0.001≤M1≤0.1, the mass percentage M2% of ethyl methyl carbonate satisfies 15≤M2≤60, the mass percentage M3% of diethyl carbonate satisfies 5≤M3≤35, the mass percentage M4% of ethylene carbonate and the mass percentage M5% of propylene carbonate satisfy 20≤M4+M5≤40.
[0097] In particular, when 20≤M2≤50 is satisfied, the lithium-ion battery has a better rate discharge capacity retention rate and a lower high-temperature storage gas production thickness change rate. In particular, when 40≤M2+M3≤66 is satisfied, the lithium-ion battery has a better rate discharge capacity retention rate and a lower high-temperature storage gas production thickness change rate. In particular, when 0.1≤(100M1+M3) / M2≤3 is satisfied, the lithium-ion battery has a better rate discharge capacity retention rate and a lower high-temperature storage gas production thickness change rate.
[0098] The lithium ion batteries of the following Examples 2-1 to 2-23 differ from those of Examples 1-21 only in that the types and mass percentages of the compounds in the electrolyte are adjusted according to Table 2, and if there is a surplus, the surplus is propyl acetate; and the mass percentage of the nickel element in the positive electrode mixture layer is adjusted according to Table 2. The performance test results of the lithium ion batteries of the various examples are shown in Table 2 below.
[0099] Table 2
[0100]
[0101] As can be seen from Table 2, the lithium-ion battery prepared in the embodiment of the present application, when the electrolyte further includes vinylene carbonate and its mass percentage satisfies 0.001≤E≤0.05, the lithium-ion battery has a better rate discharge capacity retention rate, a lower high-temperature storage gas production thickness change rate, and a lower over-discharge gas production thickness change rate. When the electrolyte further includes a compound of formula I and its mass percentage satisfies 0.01≤a≤1, the lithium-ion battery has a better rate discharge capacity retention rate, a lower high-temperature storage gas production thickness change rate, and a lower over-discharge gas production thickness change rate. When the electrolyte further includes a compound of formula II and its mass percentage satisfies 2≤b≤4, the lithium-ion battery has a better rate discharge capacity retention rate, a lower high-temperature storage gas production thickness change rate, and a lower over-discharge gas production thickness change rate.
[0102] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A non-aqueous electrolyte, characterized in that: The non-aqueous electrolyte includes a chain carbonate and a cyclic carbonate, wherein the chain carbonate includes dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, and the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate; based on the total mass of the non-aqueous electrolyte, The mass percentage of dimethyl carbonate is M1%, 0.001≤M1≤0.1; The mass percentage of the ethyl methyl carbonate is M2%, 15≤M2≤60; The mass percentage of diethyl carbonate is M3%, 5≤M3≤35; The mass percentage of the ethylene carbonate is M4%, the mass percentage of the propylene carbonate is M5%, and 20≤M4+M5≤40.
2. The non-aqueous electrolyte according to claim 1, characterized in that: The non-aqueous electrolyte satisfies at least one of the following conditions: (1)20≤M2≤50; (2) 40 ≤ M2 + M3 ≤ 66; (3) 3. The non-aqueous electrolyte according to claim 1 or 2, characterized in that The non-aqueous electrolyte includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; Based on the total mass of the non-aqueous electrolyte, the mass percentage of the lithium hexafluorophosphate is M6%, the mass percentage of the lithium bis(fluorosulfonyl)imide is M7%, 2.5≤M6≤25, 15≤M6+M7≤25.
4. The non-aqueous electrolyte according to claim 3, characterized in that The non-aqueous electrolyte satisfies:
5. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte includes vinylene carbonate; Based on the total mass of the non-aqueous electrolyte, the mass percentage of the vinylene carbonate is E%, and 0.001≤E≤0.
05.
6. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte comprises a compound of formula I: Among them, R 11 , R 12 , R 13 and R 14 are independently selected from H, F, C1 to C3 alkyl or fluorine-substituted C1 to C3 alkyl, and R 11 , R 12 , R 13 or R 14 At least one of them is a fluorine atom; Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of formula I is a%, and 0.01≤a≤1.
7. The non-aqueous electrolyte according to claim 6, characterized in that The compound of formula I includes at least one of the following compounds:
8. The non-aqueous electrolyte according to claim 1 or 2, characterized in that: The non-aqueous electrolyte comprises a compound of formula II: Among them, R 21 , R 22 , R 23 , R 24 , R 25 and R 26 Independently selected from H, F, C1 to C3 alkyl or fluorine-substituted C1 to C3 alkyl; Based on the total mass of the non-aqueous electrolyte, the mass percentage of the compound of formula II is b%, 2≤b≤4.
9. The non-aqueous electrolyte according to claim 8, characterized in that The compound of formula II includes at least one of the following compounds:
10. An electrochemical device, characterized in that: Comprising a positive electrode sheet, a negative electrode sheet and the non-aqueous electrolyte according to any one of claims 1 to 9; The positive electrode plate comprises a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector, and the negative electrode plate comprises a negative electrode current collector and a negative electrode mixture layer disposed on at least one surface of the negative electrode current collector; The positive electrode active material in the positive electrode mixture layer includes Li x Ni y M 1-y O 2-z A z , where 0.98 ≤ x ≤ 1.1, 0.53 ≤ y ≤ 0.95, 0 < z ≤ 0.05; based on the total mass of the positive electrode mixture layer, the mass percentage content of nickel element is n%, satisfying 33 ≤ n ≤ 56; The M element is selected from at least one of aluminum, magnesium, manganese, cobalt, iron, chromium, vanadium, titanium, copper, calcium, zinc, zirconium, niobium, molybdenum, strontium, antimony, tungsten and bismuth; The element A is selected from at least one of fluorine, phosphorus, sulfur, boron, silicon and chlorine.
11. An electronic device, characterized in that: An electrochemical device comprising the electrochemical device of claim 10.